2010
DOI: 10.1063/1.3517088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ag or Sb addition on the thermoelectric properties of PbTe

Abstract: In this study, the effect of Ag or Sb addition on the thermoelectric properties of PbTe including the Seebeck coefficient, the electrical resistivity, and the thermal conductivity, was studied in the temperature range from 323 to 723 K. The major carriers in the Ag-doped and the Sb-doped PbTe are holes and electrons, respectively. A degenerate semiconductor behavior in the electrical transport properties was observed in the Ag-doped, whereas the semi-metallic in the Sb-doped. It was suggested from the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 25 publications
2
39
2
Order By: Relevance
“…In Pb-deficit compositions, the highest zT of 0.81 is achieved at 623 K for the 4 mol% Sb containing sample. Both of the 1 mol% and 12 mol% Sb containing samples exhibit zT of 0.6 at 623 K. The zT values of these self-deficit Pb0.98-xSbxTe compositions are much higher than the values for pristine Pb1-xSbxTe compositions reported by Dow et al, [28]. For instance, the 4 mol% Sb containing Pb-deficit sample with the nominal composition Pb0.94Sb0.04Te exhibits zT of 0.81 at 623 K. While it was reported that, for the same dopant concentration in pristine composition (Pb0.96Sb0.04Te), the zT obtained was only 0.3 at the same temperature [28].…”
Section: Resultscontrasting
confidence: 40%
See 3 more Smart Citations
“…In Pb-deficit compositions, the highest zT of 0.81 is achieved at 623 K for the 4 mol% Sb containing sample. Both of the 1 mol% and 12 mol% Sb containing samples exhibit zT of 0.6 at 623 K. The zT values of these self-deficit Pb0.98-xSbxTe compositions are much higher than the values for pristine Pb1-xSbxTe compositions reported by Dow et al, [28]. For instance, the 4 mol% Sb containing Pb-deficit sample with the nominal composition Pb0.94Sb0.04Te exhibits zT of 0.81 at 623 K. While it was reported that, for the same dopant concentration in pristine composition (Pb0.96Sb0.04Te), the zT obtained was only 0.3 at the same temperature [28].…”
Section: Resultscontrasting
confidence: 40%
“…Both of the 1 mol% and 12 mol% Sb containing samples exhibit zT of 0.6 at 623 K. The zT values of these self-deficit Pb0.98-xSbxTe compositions are much higher than the values for pristine Pb1-xSbxTe compositions reported by Dow et al, [28]. For instance, the 4 mol% Sb containing Pb-deficit sample with the nominal composition Pb0.94Sb0.04Te exhibits zT of 0.81 at 623 K. While it was reported that, for the same dopant concentration in pristine composition (Pb0.96Sb0.04Te), the zT obtained was only 0.3 at the same temperature [28]. In the case of pristine compositions, the highest value of zT obtained at 623 K was only 0.5 for Pb0.9Sb0.1Te, which then reaches to a maximum of 0.6 at 723 K. The better TE performance of Pb-deficit samples is due to their better electrical conductivity and lower thermal conductivity when compared to pristine Pb1-xSbxTe [28].…”
Section: Resultscontrasting
confidence: 40%
See 2 more Smart Citations
“…The thermal conductivity values increases from 0.54-0.90 W/mK over temperature range of 298-773 K, due to electron-phonon nonequilibrium at high electron temperatures. 20 This can be explained using the WiedemannFranz law, 21 K e ¼ rLT e , where r is charge conductivity, L is the Lorenz number (¼2.45 E-8 WXK À2 ), 22 and T e is the electronic temperature. In our samples, the contribution of phonons is dominant over the entire temperature range, as evidenced from electronic thermal conductivity values ( Fig.…”
Section: Thermoelectric Properties Of Nanoporous Three-dimensional Grmentioning
confidence: 99%